Use of continuous medical and pharmaceutical education system for cancer alertness formation in practice of otorhinolaryngologists of the Orenburg region - Elena D. Lutsay; Maxim I. Anikin; Nuria I. Murtazina (Наука и инновации в медицине, 2020)
Objectives - to present practical application issues of distance education technologies in the training of health workers for the additional professional development program "Cancer alertness issues in practice of otorhinolaryngologists". The relevance of the program development and implementation in the Orenburg region is of particular importance, due to the fact that the regional cancer morbidity rate exceeds the average value in Russia. Results. The professional development program was prepared by the teaching staff of the Otorhinolaryngology Department of the Orenburg State Medical University and is meant for specialists certificated in "Otorhinolaryngology", "General Medical Practice (Family Medicine)". The program includes training materials, entry level tests that allow determining the specialists' initial knowledge level in the issues of early detection of ENT-organs malignant neoplasms, and the final progress check. Conclusion. The program allows doctors-otorhinolaryngologists to increase the professional competencies level in the field of malignant neoplasms cancer alertness; it was implemented in the education and information environment of the university on the basis of the "1C: Educational Organization" platform at the beginning of this year.